Perbandingan Aromaterapi Inhalasi Lemon dan Peppermint Terhadap Mual dan Muntah Ibu Hamil Trimester I di PMB Melinda Kabupaten Way Kanan Tahun 2024 - Septiara Erfika Putri; Riona Sanjaya; Iis Tri Utami; Rini Wahyuni (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Nausea and vomiting during pregnancy, or morning sickness, are common conditions affecting approximately 70–80% of pregnant women, typically occurring between 5 and 12 weeks of gestation. Aromatherapy using lemon and peppermint essential oils is considered a complementary therapy for reducing these symptoms. In 2023, 76 cases (52.4%) of nausea and vomiting were recorded among first-trimester pregnant women at PMB Melinda. This study aimed to compare the effects of lemon and peppermint aromatherapy inhalation on nausea and vomiting in first-trimester pregnant women. Using a quantitative quasi-experimental design with a three-group pretest-posttest approach, the study involved 36 participants divided into three groups: 12 received lemon aromatherapy, 12 received peppermint aromatherapy, and 12 received vitamin B6 supplementation. Data were collected using the PUQI observation sheet and analyzed using univariate and bivariate methods with a paired sample t-test. The results showed that the mean nausea and vomiting score before lemon aromatherapy was 8.75, which decreased to 4.67 after the intervention. In the peppermint group, the mean score decreased from 8.08 to 3.83, while in the vitamin B6 group, it reduced from 8.75 to 6.42. Statistical analysis revealed that both lemon and peppermint aromatherapy significantly reduced nausea and vomiting (p = 0.000), while no significant difference was found between the two treatments (p = 0.756). The study concludes that both lemon and peppermint aromatherapy are effective non-pharmacological alternatives for managing nausea and vomiting during early pregnancy.